The Evaluation of Mode Shift Preference within Bus Rapid Transit-oriented Development Context - Lutfi Prayogi; Finta Lissimia (International Journal of Built Environment and Scientific Research, 2021)
Bus rapid transit (BRT) has been acknowledged as a mode of transit that is appropriate to be constructed in conjunction with transit-oriented development (TOD). In order to evaluate the occurrence of a TOD with BRT systems as its component, evaluating the passengers’ mode shift triggered by the provision of the BRT systems is one approach that can be taken. Within the mentioned type of TOD, the built environment should support, or even more trigger, the passengers’ mode shift into taking the BRT systems. This article evaluates the mode shift preference of Transjakarta BRT passengers. This article also evaluates the heterogeneity of mode shift preference among various groups of Transjakarta passengers. This article qualitatively describes the mode shift preference, while the data was collected, processed, and presented in quantitative manners. Information regarding the mode shift preference is collected through an indirect interview. The statistics of the mode shift preference is processed using simple statistical analysis and Bartlett’s test for variance heterogeneity. It is found that the role of the built environment in supporting Transjakarta passengers’ mode shift into taking Transjakarta is relatively low. It is also found that the variance of the mode shift preference is homogeneous across various groups of Transjakarta passengers. This article concludes that the envisioned bus rapid transit-oriented development (BRTOD) hasn't been fully occurring in areas around Transjakarta corridors.